2023
DOI: 10.3390/jpm13111544
|View full text |Cite
|
Sign up to set email alerts
|

Condylar Positional Changes in Skeletal Class II and Class III Malocclusions after Bimaxillary Orthognathic Surgery

Víctor Ravelo,
Gabriela Olate,
Marcio de Moraes
et al.

Abstract: Orthognathic surgery is indicated to modify the position of the maxillomandibular structure; changes in the mandibular position after osteotomy can be related to changes in the position of the mandibular condyle in the articular fossa. The aim of this study was to determine changes produced in the mandibular condyle 6 months after orthognathic surgery. A cross-sectional study was conducted that included subjects who had undergone bimaxillary orthognathic surgery to treat dentofacial deformity of Angle class II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…On the other hand, there were studies that reported no change in joint space or a decrease in posterior joint space compared to pre-surgery levels. 20 , 21 These studies targeted patients undergoing SSO, introducing potential variations from our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there were studies that reported no change in joint space or a decrease in posterior joint space compared to pre-surgery levels. 20 , 21 These studies targeted patients undergoing SSO, introducing potential variations from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Orthognathic surgery is indicated to modify the position of the maxillomandibular structure, which may cause changes in the sagittal position of the mandibular condyle in individuals with retrognathism and mandibular prognathism. In the context of orthognathic surgery, anterior open bite (AOB) is an easily recognized malocclusion and presents only aesthetic and functional problems [1,2]. Its etiology is multifactorial, including heredity, oral habits, unfavorable growth patterns, and enlarged lymphatic tissue along with mouth breathing and oral functional matrices.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, open bite treatment involves preventive treatments, eliminating harmful habits, and correcting the posture of soft tissues through the use of palatal bars or orthopedic devices, including corrective mechanics, extractions, elastics, alignment, and leveling, headgear, and orthognathic surgeries [1,2]. The literature is controversial regarding definitions, etiology, and forms of treatment [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation